Composite cathode material, preparation method thereof and battery

CN123017921APending Publication Date: 2026-10-30NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611139722.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]针对全固态电池中三元正极材料的界面稳定性问题,通过进行表面包覆,一定程度上改善了正极材料表面与固态电解质之间的界面的稳定性;但是,当前的包覆工艺普遍存在表面包覆物分布不均匀的缺陷,这会导致不同区域的三元正极材料反应强度差异化,进而加剧电池循环过程中界面副反应,其结果表现为电池实际容量偏低,且长期循环稳定性不足

Benefits of technology

(1)本发明提供的复合正极材料中,第一包覆层在所述正极材料核的表面呈岛状分布,增大了正极材料核的表面粗糙度,有利于第二包覆层与第一包覆层的咬合接触,从而提升了第二包覆层在正极材料核和/或第一包覆层外部的包覆效果;因此,所述复合正极材料中,第一包覆层与第二包覆层对正极材料的包覆较为均匀且具有较高的包覆率;因此,包含所述复合正极材料的电池在使用时,正极材料的表面不同区域的反应强度差异较小,复合正极材料和固态电解质之间的副反应得到了充分的抑制;所以,包含所述复合正极材料的电池表现出较高的容量与优异的循环稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017921A_ABST
    Figure CN123017921A_ABST
Patent Text Reader

Abstract

The application provides a composite positive electrode material, a preparation method thereof and a battery. The composite positive electrode material comprises a positive electrode material core, an island-shaped first coating layer on the surface of the positive electrode material core, and a second coating layer at least partially coated on the outside of the positive electrode material core and / or the first coating layer; the first coating layer comprises a first coating material, and the first coating material comprises any one or a combination of at least two of cobalt oxide, cobalt arsenide, zirconate or silicate; the second coating layer comprises a second coating material, and the second coating material comprises boric acid and / or silicic acid. The island-shaped distribution of the first coating layer optimizes the combination with the second coating layer, realizes uniform and efficient coating, the first coating layer contains the first coating material with high hardness, the internal strength and pressure resistance are improved, the second coating layer contains the second coating material with low hardness and flexibility, flexible contact with the solid-state electrolyte is realized, and the performance of the composite positive electrode material is synergistically improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery technology, and relates to a composite cathode material, and more particularly to a composite cathode material, its preparation method, and a battery. Background Technology

[0002] Lithium-ion batteries have a series of advantages such as high specific energy, high operating voltage, good safety, and no memory effect. They are not only widely used as power sources for portable electronic products such as laptops, digital cameras, mobile phones, and camcorders, but will also become one of the main power sources for electric bicycles, electric motorcycles, and electric vehicles.

[0003] As one of the core components of a battery, the cathode material plays a crucial role in the overall performance of the battery. Currently, ternary cathode materials are widely used. However, when applied to all-solid-state batteries, the chemical properties of the ternary cathode material and the solid electrolyte are incompatible, triggering interfacial reactions and making it difficult for the interfacial stability of the ternary cathode material to meet practical requirements.

[0004] In order to improve the interfacial stability of ternary cathode materials, those skilled in the art have adopted a series of modification methods. One common method is to improve the interfacial stability of ternary cathode materials by coating the surface of the ternary cathode materials.

[0005] To address the interfacial stability issue of ternary cathode materials in all-solid-state batteries, surface coating has improved the interfacial stability between the cathode material surface and the solid electrolyte to some extent. However, current coating processes generally suffer from uneven distribution of the surface coating, which leads to differences in the reaction intensity of the ternary cathode material in different regions. This, in turn, exacerbates interfacial side reactions during battery cycling, resulting in lower actual battery capacity and insufficient long-term cycling stability.

[0006] Therefore, developing and designing a novel composite cathode material and its preparation method is crucial for batteries. Summary of the Invention

[0007] To address the shortcomings of existing technologies, the present invention aims to provide a composite cathode material, its preparation method, and a battery. The composite cathode material provided by the present invention optimizes the bonding with the second coating layer through the island-like distribution of the first coating layer, achieving uniform and efficient coating. In addition, the first coating layer contains a high-hardness first coating material, which improves internal strength and compressive strength, while the second coating layer contains a low-hardness, flexible second coating material, achieving flexible contact with the solid electrolyte. The synergistic effect of the two enhances cycle stability while ensuring the electrochemical activity of the composite cathode material. Therefore, the battery containing the composite cathode material exhibits high capacity and excellent cycle stability.

[0008] To achieve this objective, the present invention adopts the following technical solution: In a first aspect, the present invention provides a composite cathode material, the composite cathode material comprising a cathode material core, a first coating layer having island-like distributions on the surface of the cathode material core, and a second coating layer at least partially covering the cathode material core and / or the outside of the first coating layer; The core of the cathode material is composed of lithium transition metal oxide; The first coating layer includes a first coating material, which includes any one or a combination of at least two of cobalt oxide, cobalt arsenide, zirconate, or silicate. The second coating layer includes a second coating material, which includes boric acid and / or silica.

[0009] In the composite cathode material provided by this invention, the first coating layer is distributed in an island-like pattern on the surface of the cathode material core, increasing the surface roughness of the cathode material core. This facilitates the interlocking contact between the second coating layer and the first coating layer, thereby improving the coating effect of the second coating layer on the cathode material core and / or the outside of the first coating layer. Therefore, in the composite cathode material, the first and second coating layers coat the cathode material relatively uniformly and have a high coating rate. Consequently, when the battery containing the composite cathode material is in use, the reaction intensity difference between different regions on the surface of the cathode material is small, and the side reactions between the composite cathode material and the solid electrolyte are sufficiently suppressed. Therefore, the battery containing the composite cathode material exhibits high capacity and excellent cycle stability.

[0010] In the composite cathode material provided by the present invention, the first coating material in the first coating layer includes any one or a combination of at least two of cobalt oxide, cobalt arsenide, zirconate or silicate. These materials have a Mohs hardness of 3.0 to 9.0. The first coating material with higher hardness has rigidity, which improves the internal strength of the composite cathode material, thereby improving the compressive strength of the composite cathode material and the cycle stability of the composite cathode material.

[0011] In the composite cathode material provided by the present invention, the second coating layer includes boric acid and / or silicic acid. These materials have a Mohs hardness of 1.0 to 3.0. Therefore, the second coating material with lower hardness is flexible, which improves the flexibility of the second coating layer and realizes flexible contact between the composite cathode material and the solid electrolyte, thereby enhancing the cycle stability of the composite cathode material.

[0012] In summary, the composite cathode material provided by this invention optimizes the bonding with the second coating layer through the island-like distribution of the first coating layer, achieving uniform and efficient coating. Furthermore, the first coating layer contains a high-hardness first coating material, enhancing internal strength and compressive strength, while the second coating layer contains a low-hardness, flexible second coating material, enabling flexible contact with the solid electrolyte. The synergistic effect of these two materials enhances cycle stability while ensuring the electrochemical activity of the composite cathode material. Therefore, batteries containing this composite cathode material exhibit high capacity and excellent cycle stability.

[0013] Preferably, the first coating layer further includes a third coating material, which includes any one or a combination of at least two of lithium cobalt oxide, lithium zirconate, or lithium silicate; the first coating material and the third coating material do not contain the same material. And / or, the second coating layer further includes a fourth coating material, the fourth coating material including lithium borate and / or lithium silicate.

[0014] Preferably, the molar ratio of the first coating material to the third coating material in the first coating layer is x:(10-x), and x is 0.1~4.

[0015] Preferably, the molar ratio of the second coating material to the fourth coating material in the second coating layer is y:(10-y), and y is 0.1~4.

[0016] Preferably, the first coating layer and the second coating layer cover more than 80% of the surface area of ​​the cathode material core.

[0017] In a second aspect, the present invention provides a method for preparing the composite cathode material described in the first aspect, the method comprising: (1) After mixing the positive electrode material and the first coating raw material, a first heat treatment is carried out in an oxygen-containing atmosphere to obtain the first material; (2) After mixing the first material obtained in step (1) with the second coating material, a second heat treatment is carried out in an oxygen-containing atmosphere to obtain a composite cathode material; The cathode material is a lithium transition metal oxide cathode material; The temperature of the first heat treatment is less than the melting point of the first coating material; The melting point of the second coating material is less than the temperature of the second heat treatment; The temperature of the first heat treatment is 600℃~900℃, and the time is 10h~14h; The second heat treatment is performed at a temperature of 300℃ to 600℃ for a time of 10h to 14h.

[0018] Preferably, the melting point of the second coating material is less than the temperature of the second heat treatment, which is less than the temperature of the first heat treatment, which is less than the melting point of the first coating material.

[0019] Preferably, the method for preparing the cathode material includes: mixing the cathode material precursor with a lithium source, and then sintering the mixture to obtain the cathode material; The temperature of the first heat treatment is lower than the temperature of the sintering.

[0020] Preferably, the cathode material in step (1) is a polycrystalline material, including nickel-cobalt-manganese ternary cathode material, and the D50 particle size of the polycrystalline material is 2μm~15μm; the average particle size of the primary particles of the polycrystalline material is 300nm~1.1μm; in step (1), the D50 particle size of the first coated raw material is smaller than the average particle size of the primary particles of the polycrystalline material; Alternatively, the cathode material in step (1) is a single crystal material, including nickel-cobalt-manganese ternary cathode material, and the D50 particle size of the single crystal material is 1.1μm~6μm; the D50 particle size of the first coated raw material in step (1) is smaller than the D50 particle size of the single crystal material. Alternatively, the cathode material in step (1) is a quasi-single crystal material, including nickel-cobalt-manganese ternary cathode material, and the D50 particle size of the quasi-single crystal material is 2μm~15μm; in step (1), the D50 particle size of the first coated raw material is smaller than the average particle size of the primary particles of the quasi-single crystal material.

[0021] Preferably, in step (1), the D50 particle size of the first coated raw material is 30 nm to 1 μm.

[0022] Preferably, in step (2), the D50 particle size of the second coated raw material is ≤15μm.

[0023] Preferably, in the mixing process described in step (1), the mass ratio of the positive electrode material to the first coating material is 1:(0.005~0.05); And / or, in the mixing described in step (2), the mass ratio of the first material obtained in step (1) to the second coating material is 1:(0.0005~0.005); And / or, in step (1), the first coating material includes any one or a combination of at least two of cobalt oxide, cobalt arsenide, zirconate or silicate; And / or, in step (2), the second coating material includes boric acid and / or silicic acid.

[0024] Thirdly, the present invention provides a battery comprising the composite positive electrode material described in the first aspect, wherein the battery is an all-solid-state battery.

[0025] Compared with the prior art, the present invention has the following beneficial effects: (1) In the composite cathode material provided by the present invention, the first coating layer is distributed in an island-like manner on the surface of the cathode material core, which increases the surface roughness of the cathode material core and facilitates the interlocking contact between the second coating layer and the first coating layer, thereby improving the coating effect of the second coating layer on the cathode material core and / or the outside of the first coating layer; therefore, in the composite cathode material, the coating of the cathode material by the first coating layer and the second coating layer is relatively uniform and has a high coating rate; therefore, when the battery containing the composite cathode material is used, the reaction intensity difference in different areas of the cathode material surface is small, and the side reactions between the composite cathode material and the solid electrolyte are sufficiently suppressed; therefore, the battery containing the composite cathode material exhibits high capacity and excellent cycle stability.

[0026] (2) In the composite cathode material provided by the present invention, the first coating material in the first coating layer includes any one or a combination of at least two of cobalt oxide, cobalt arsenide, zirconate or silicate. The Mohs hardness of these materials is 3.0 to 9.0. The first coating material with higher hardness has rigidity, which improves the internal strength of the composite cathode material, thereby improving the compressive strength of the composite cathode material and improving the cycle stability of the composite cathode material.

[0027] (3) In the composite cathode material provided by the present invention, the second coating material in the second coating layer includes boric acid and / or silicic acid. The Mohs hardness of these materials is 1.0 to 3.0. Therefore, the second coating material with lower hardness has flexibility, which improves the flexibility of the second coating layer and realizes flexible contact between the composite cathode material and the solid electrolyte, thereby enhancing the cycle stability of the composite cathode material. Attached Figure Description

[0028] Figure 1 This is a SEM image of the cathode material in Example 1.

[0029] Figure 2 This is a SEM image of the composite cathode material in Example 1.

[0030] Figure 3 This is a SEM image of the cathode material in Example 11.

[0031] Figure 4 These are XPS images of the composite cathode materials provided in Example 1 and Comparative Example 1.

[0032] Figure 5 This is an XPS image of the first coating layer in the composite cathode material provided in Example 8.

[0033] Figure 6 This is an XPS image of the second coating layer in the composite cathode material provided in Example 8.

[0034] Figure 7 The specific capacity curves are those of all-solid-state mold batteries prepared with the composite cathode materials provided in Examples 1, 3, 8, 10 and Comparative Example 3.

[0035] Figure 8 This is an SEM image of the first material obtained in step (2) of the preparation method provided in Example 1. Detailed Implementation

[0036] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0037] In one embodiment, the present invention provides a composite cathode material, the composite cathode material comprising a cathode material core, a first coating layer having island-like distributions on the surface of the cathode material core, and a second coating layer at least partially covering the cathode material core and / or the first coating layer. The core of the cathode material is composed of lithium transition metal oxide; The first coating layer includes a first coating material, which includes any one or a combination of at least two of cobalt oxide, cobalt arsenide, zirconate, or silicate. The second coating layer includes a second coating material, which includes boric acid and / or silica.

[0038] In some embodiments, the first coating material comprises any one or a combination of at least two of cobalt oxide, cobalt arsenide, zirconate, or silicate. Typical but non-limiting combinations include a combination of cobalt oxide and cobalt arsenide, a combination of cobalt oxide and zirconate, a combination of zirconate and silicate, a combination of cobalt oxide and silicate, or a combination of cobalt oxide, zirconate, and silicate.

[0039] In this invention, the cobalt oxide refers to a compound composed of cobalt and oxygen elements, excluding lithium cobalt oxide.

[0040] In some embodiments, the cobalt oxide in the first coating material includes any one or a combination of at least two of cobalt trioxide, cobalt monoxide, or cobalt trioxide. Typical but non-limiting combinations include a combination of cobalt trioxide and cobalt monoxide, a combination of cobalt monoxide and cobalt trioxide, a combination of cobalt trioxide and cobalt trioxide, or a combination of cobalt trioxide, cobalt monoxide, and cobalt trioxide.

[0041] In some embodiments, the zirconate in the first coating material includes any one or a combination of at least two of calcium zirconate, strontium zirconate, barium zirconate, lanthanum zirconate, or yttrium zirconate. Typical but non-limiting combinations include combinations of calcium zirconate and strontium zirconate, combinations of strontium zirconate and barium zirconate, combinations of lanthanum zirconate and yttrium zirconate, or combinations of calcium zirconate, strontium zirconate, and barium zirconate.

[0042] In some embodiments, the silicate in the first coating material includes zirconium silicate and / or sodium silicate.

[0043] In the composite cathode material provided by this invention, the first coating layer is distributed in an island-like pattern on the surface of the cathode material core, increasing the surface roughness of the cathode material core. This facilitates the interlocking contact between the second coating layer and the first coating layer, thereby improving the coating effect of the second coating layer on the cathode material core and / or the outside of the first coating layer. Therefore, in the composite cathode material, the first and second coating layers coat the cathode material relatively uniformly and have a high coating rate. Consequently, when the battery containing the composite cathode material is in use, the reaction intensity difference between different regions on the surface of the cathode material is small, and the side reactions between the composite cathode material and the solid electrolyte are sufficiently suppressed. Therefore, the battery containing the composite cathode material exhibits high capacity and excellent cycle stability.

[0044] The cathode material core described in this invention is preferably a layered transition metal oxide. This invention has been validated using a high-nickel layered ternary material (nickel content ≥ 60%) as an example. However, based on the coating mechanism of this invention, those skilled in the art can reasonably expect that when applied to other lithium transition metal oxides (such as lithium nickel cobalt aluminum oxide or lithium-rich manganese-based cathode materials), the coating layer structure of this invention can also achieve a synergistic improvement in capacity and cycle stability.

[0045] In the composite cathode material provided by this invention, the first coating material in the first coating layer includes any one or a combination of at least two of cobalt oxide, cobalt arsenide, zirconate, or silicate. The Mohs hardness of these materials is 3.0 to 9.0, for example, it can be 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, or 9.0, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable. The first coating material with higher hardness has rigidity, which improves the internal strength of the composite cathode material, thereby improving the compressive strength of the composite cathode material and the cycle stability of the composite cathode material.

[0046] In the composite cathode material provided by this invention, the second coating layer comprises boric acid and / or silicic acid, which have a Mohs hardness of 1.0 to 3.0, for example, 1.0, 1.5, 2.0, 2.5 or 3.0, but are not limited to the listed values; other unlisted values ​​within this range are also applicable. The lower hardness of the second coating material enhances its flexibility, thereby improving the flexibility of the second coating layer and enabling flexible contact between the composite cathode material and the solid electrolyte, thus enhancing the cycle stability of the composite cathode material.

[0047] In summary, the composite cathode material provided by this invention optimizes the bonding with the second coating layer through the island-like distribution of the first coating layer, achieving uniform and efficient coating. Furthermore, the first coating layer contains a high-hardness first coating material, enhancing internal strength and compressive strength, while the second coating layer contains a low-hardness, flexible second coating material, enabling flexible contact with the solid electrolyte. The synergistic effect of these two materials enhances cycle stability while ensuring the electrochemical activity of the composite cathode material. Therefore, batteries containing this composite cathode material exhibit high capacity and excellent cycle stability.

[0048] In some embodiments, the first coating layer further includes a third coating material, which includes any one or a combination of at least two of lithium cobalt oxide, lithium zirconate, or lithium silicate; the first coating material and the third coating material do not contain the same material; And / or, the second coating layer further includes a fourth coating material, the fourth coating material including lithium borate and / or lithium silicate.

[0049] In this invention, the third coating material includes any one or a combination of at least two of lithium cobalt oxide, lithium zirconium oxide, or lithium silicate. Typical but non-limiting combinations include combinations of lithium cobalt oxide and lithium zirconium oxide, combinations of lithium zirconium oxide and lithium silicate, combinations of lithium cobalt oxide and lithium silicate, or combinations of lithium cobalt oxide, lithium zirconium oxide, and lithium silicate.

[0050] In this invention, the third coating material (lithium cobalt oxide (LiCoO2), lithium zirconate (Li2ZrO3), or lithium silicate (Li2SiO3)) is a lithium oxide product generated after a portion of the first coating raw material (cobalt oxide, zirconate, or silicate) undergoes an in-situ lithiation reaction with the residual lithium compound on the core surface of the cathode material during the first heat treatment in an oxygen-containing atmosphere.

[0051] In this invention, the third coating material comprises any one or a combination of at least two of lithium cobalt oxide, lithium zirconate, or lithium silicate; therefore, the ionic conductivity of the third coating material is >10. -7 S / cm, for example, could be 1.1 × 10 -7 S / cm, 1.2×10 -7 S / cm, 1.4×10-7 S / cm, 1.6×10 -7 S / cm, 1.8×10 -7 S / cm, 2.0×10 -7 S / cm, 2.2×10 -7 S / cm, 2.4×10 -7 S / cm, 2.6×10 -7 S / cm, 2.8×10 -7 S / cm or 3.0×10 -7 S / cm, but not limited to the listed values; other unlisted values ​​within this range also apply.

[0052] The third coating material provided by this invention has an ionic conductivity >10. -7 S / cm is mainly used to provide lithium-ion transport channels and has poor reactivity with electrolyte. While ensuring the ionic conductivity of composite cathode material, it reduces the risk of side reactions between composite cathode material and electrolyte, thereby helping to improve battery capacity and cycle stability.

[0053] In this invention, the fourth coating material (lithium borate and / or lithium silicate) is a lithium oxide product generated by the in-situ lithiation reaction between a portion of the third coating raw material (boric acid and / or silicate) and the residual lithium compound on the core surface of the cathode material during the second heat treatment process in an oxygen-containing atmosphere.

[0054] In this invention, the fourth coating material comprises lithium borate and / or lithium silicate, therefore the ionic conductivity of the fourth coating material is >10. -7 S / cm, for example, could be 1.1 × 10 -7 S / cm, 1.2×10 -7 S / cm, 1.4×10 -7 S / cm, 1.6×10 -7 S / cm, 1.8×10 -7 S / cm, 2.0×10 -7 S / cm, 2.2×10 -7 S / cm, 2.4×10 -7 S / cm, 2.6×10 -7 S / cm, 2.8×10 -7 S / cm or 3.0×10 -7 S / cm, but not limited to the listed values; other unlisted values ​​within this range also apply.

[0055] The fourth coating material provided by this invention has an ionic conductivity >10. -7S / cm is mainly used to provide lithium-ion transport channels and has poor reactivity with electrolyte. While ensuring the ionic conductivity of composite cathode material, it reduces the risk of side reactions between composite cathode material and electrolyte, thereby helping to improve battery capacity and cycle stability.

[0056] In some implementations, the first coating material and the fourth coating material are the same, and XPS characterization of the etching depth can confirm that the same first coating material and the fourth coating material are located in the first coating layer and the second coating layer, respectively.

[0057] In some implementations, the molar ratio of the first coating material to the third coating material in the first coating layer is x:(10-x), where x is 0.1 to 4. For example, the molar ratio of the first coating material to the third coating material can be 0.1:9.9, 0.5:9.5, 1:9, 1.5:8.5, 2:8, 2.5:7.5, 3:7, 3.5:6.5, or 4:6, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0058] In this invention, by limiting the molar ratio of the first coating material to the third coating material in the first coating layer to x:(10-x) and x to 0.1~4, a small amount of the first coating material with higher hardness can ensure the internal strength of the cathode material, while a larger amount of the third coating material has stronger conductivity and can form a cross-conductive network channel, thereby enhancing the compressive strength of the composite cathode material and improving its electrochemical performance.

[0059] In some implementations, the molar ratio of the second coating material to the fourth coating material in the second coating layer is y:(10-y), where y is 0.1 to 4. For example, the molar ratio of the second coating material to the fourth coating material can be 0.1:9.9, 0.5:9.5, 1:9, 1.5:8.5, 2:8, 2.5:7.5, 3:7, 3.5:6.5, or 4:6, but is not limited to the listed values; other unlisted values ​​within this range are also applicable.

[0060] In this invention, by limiting the molar ratio of the second coating material to the fourth coating material in the second coating layer to y:(10-y) and y to 0.1~4, a small amount of the second coating material with lower hardness and higher flexibility can alleviate the stress between the composite cathode materials and enhance the contact between the composite cathode material and the solid electrolyte. The product of more fourth coating material has better ionic conductivity, which can improve the ion conduction ability of the composite cathode material and thus improve the electrochemical performance of the composite cathode material.

[0061] In some implementations, the first coating layer and the second coating layer cover more than 80% of the surface area of ​​the cathode material core.

[0062] In this invention, the first coating layer and the second coating layer cover more than 80% of the surface area of ​​the positive electrode material core, that is, more than 80% coating rate, which has a high coating rate; when the battery containing the composite positive electrode material is used, the reaction intensity difference between different areas of the surface of the composite positive electrode material is small, and the side reactions between the composite positive electrode material and the solid electrolyte are sufficiently suppressed.

[0063] In some implementations, the coverage rate is calculated as the ratio of the total molar amount of coated elements in the first and second coating layers to the total molar amount of all elements except lithium and oxygen in the first and second coating layers, i.e.: Coverage = n 包覆元素 / n 非Li和O ; Where, n 包覆元素 This represents the sum of the molar amounts of the coating elements contained in the first and second coating layers. Coating elements refer to the sum of the molar amounts of all elements (e.g., cobalt, zirconium, boron, silicon, etc.) except for lithium, oxygen, nickel, manganese, and cathode material doping elements (e.g., magnesium, titanium, calcium, strontium, etc.); n 非Li和O It represents the sum of the molar amounts of all elements except lithium and oxygen contained in the first and second coating layers.

[0064] It should be noted that the cathode material core does not necessarily contain doped elements. Whether the cathode material core contains doped elements can be determined by ICP combined with EDS testing. Both the cathode material core and the coating layer contain cobalt; here, cobalt is included in the coating layer elements for calculation.

[0065] The specific testing steps are as follows: (1) Determination of the total molar amount of coating elements: Take a composite cathode material sample and use X-ray photoelectron spectroscopy (XPS) combined with Ar + Ion etching was used for depth profiling, with an etching depth set at 100 nm. Using XPS full-spectrum scanning and high-resolution narrow-spectrum quantitative analysis, the atomic percentage concentrations of all elements except lithium and oxygen in the first and second coating layers were obtained. Combined with parameters such as the etched area and material density, and excluding carbon as an interfering impurity, the molar amounts of each element were calculated. Finally, the molar amounts of all elements in all coating layers except lithium, oxygen, nickel, manganese, and dopants were summed to obtain n. 包覆元素 .

[0066] (2) Determination of the total molar amount of all elements in the coating layer except lithium and oxygen: Take a positive electrode material sample and use X-ray photoelectron spectroscopy (XPS) combined with Ar +Ion etching was used for depth profiling, with an etching depth set at 100 nm. Using XPS full-spectrum scanning and high-resolution narrow-spectrum quantitative analysis, the atomic percentage concentrations of all elements except lithium and oxygen in the first and second coating layers were obtained. Combined with parameters such as the etched area and material density, and excluding carbon as an interfering impurity, the molar amounts of each element were calculated. The molar amounts of all elements except lithium and oxygen in all coating layers were then summed to obtain n. 非Li和O .

[0067] (3) Substitute the values ​​obtained in steps (1) and (2) into the above formula to calculate the coverage rate.

[0068] In another embodiment, the present invention provides a method for preparing the above-mentioned composite cathode material, the method comprising: (1) After mixing the positive electrode material and the first coating raw material, a first heat treatment is carried out in an oxygen-containing atmosphere to obtain the first material; (2) After mixing the first material obtained in step (1) with the second coating material, a second heat treatment is carried out in an oxygen-containing atmosphere to obtain a composite cathode material; The cathode material is a lithium transition metal oxide cathode material; The temperature of the first heat treatment is less than the melting point of the first coating material; The melting point of the second coating material is less than the temperature of the second heat treatment; The temperature of the first heat treatment is 600℃~900℃, and the time is 10h~14h; The second heat treatment is performed at a temperature of 300℃ to 600℃ for a time of 10h to 14h.

[0069] In this invention, the temperature of the first heat treatment is 600℃~900℃, for example, it can be 601℃, 625℃, 650℃, 675℃, 700℃, 725℃, 750℃, 775℃, 800℃, 850℃ or 900℃, but it is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0070] In this invention, the first heat treatment time is 10 to 14 hours, for example, it can be 10 hours, 10.5 hours, 11 hours, 11.5 hours, 12 hours, 12.5 hours, 13 hours, 13.5 hours or 14 hours, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0071] In this invention, the temperature of the second heat treatment is 300℃~600℃, for example, it can be 300℃, 350℃, 400℃, 450℃, 500℃, 550℃, 590℃ or 600℃, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0072] In this invention, the second heat treatment time is 10 to 14 hours, for example, it can be 10 hours, 10.5 hours, 11 hours, 11.5 hours, 12 hours, 12.5 hours, 13 hours, 13.5 hours or 14 hours, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0073] In some embodiments, a heating process is further performed before the first heat treatment at a heating rate of 1 to 10 °C / min. The heating rate may be, for example, 1 °C / min, 2 °C / min, 3 °C / min, 4 °C / min, 5 °C / min, 6 °C / min, 7 °C / min, 8 °C / min, 9 °C / min or 10 °C / min, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0074] In some embodiments, the second heat treatment is further performed by a heating process at a heating rate of 1 to 10 °C / min. The heating rate may be, for example, 1 °C / min, 2 °C / min, 3 °C / min, 4 °C / min, 5 °C / min, 6 °C / min, 7 °C / min, 8 °C / min, 9 °C / min or 10 °C / min, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0075] In some implementations, the volume fraction of oxygen in the oxygen-containing atmosphere in step (1) is not less than 60%, for example, it can be 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 100%, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0076] In some implementations, the volume fraction of oxygen in the oxygen-containing atmosphere in step (2) is not less than 60%, for example, it can be 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 100%, but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0077] In the method for preparing the composite cathode material provided by the present invention, during the first heat treatment, part of the first coating raw material reacts to form the third coating material, and part of the first coating raw material does not react and exists as the first coating material in the first coating layer.

[0078] In the preparation method of the composite cathode material provided by the present invention, during the second heat treatment, part of the second coating raw material reacts to form a fourth coating material, and part of the second coating raw material does not react and exists as the second coating material in the second coating layer.

[0079] In the method for preparing the composite cathode material provided by the present invention, the first coating material and the fourth coating material can be the same material, and when they are the same, the first coating raw material and the second coating raw material are different.

[0080] In the preparation method provided by this invention, the temperature of the first heat treatment is lower than the melting point of the first coating material, ensuring that the first coating material does not melt during the first heat treatment. Instead, it adheres to the surface of the positive electrode material after reacting with the residual lithium compound on the surface of the positive electrode material, forming an island-like distribution on the surface of the positive electrode material. This achieves coating of the positive electrode material while increasing the surface roughness of the positive electrode material. In addition, the melting point of the second coating material is lower than the temperature of the second heat treatment, ensuring that the second coating material can melt during the second heat treatment. The melted second coating material has high fluidity, thereby achieving coating of at least part of the core of the positive electrode material and / or the outside of the first coating layer, increasing the uniformity of coating and improving the coating rate.

[0081] In the preparation method provided by the present invention, the time and temperature of the first heat treatment are designed according to the first coating material, so that in the first heat treatment, part of the first coating material reacts to form a third coating material, and part of the first coating material does not react, forming a first coating layer containing the third coating material and the first coating material.

[0082] In the preparation method provided by the present invention, the time and temperature of the second heat treatment are designed according to the second coating material, so that in the second heat treatment, part of the second coating material reacts to form the fourth coating material, and part of the second coating material does not react, forming a first coating layer containing the fourth coating material and the second coating material.

[0083] In some embodiments, the melting point of the second coating material is less than the temperature of the second heat treatment, which is less than the temperature of the first heat treatment, which is less than the melting point of the first coating material. And / or, the method for preparing the cathode material includes: mixing the cathode material precursor with a lithium source and then sintering it to obtain the cathode material; The temperature of the first heat treatment is lower than the temperature of the sintering.

[0084] In this invention, by limiting the melting point of the second coating material to < the temperature of the second heat treatment to < the temperature of the first heat treatment to < the melting point of the first coating material, the temperature of the second heat treatment is further limited to < the temperature of the first heat treatment, thus avoiding overheating during the second heat treatment and reducing the risk of metal leaching.

[0085] In this invention, by limiting the temperature of the first heat treatment to be lower than the sintering temperature, the problem of over-burning of the positive electrode material during the first heat treatment, thereby preventing metal leaching, is avoided.

[0086] In some implementations, the cathode material in step (1) can be a high-nickel ternary cathode material or a medium-nickel ternary cathode material.

[0087] In some implementations, the chemical formula of the cathode material in step (1) includes LiNi. a Co b Mn c O2X d Wherein, 0.6≤a≤0.96, 0≤b≤0.4, 0≤c≤0.4, and 0≤d≤0.05. X includes one or more of Mg, Ti, Ga, Nb, Mo, Sn, Sb, Ta, W, K, Ca, Zn, Sr, Y, Ba, La, and Ce.

[0088] In this invention, 0.6≤a≤0.96, and the value of a can be, for example, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90 or 0.96, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0089] In this invention, 0 ≤ b ≤ 0.4, and the value of b can be, for example, 0, 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35 or 0.40, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0090] In this invention, 0 ≤ c ≤ 0.4, and the value of c can be, for example, 0, 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35 or 0.40, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0091] In some embodiments, the cathode material precursor includes a hydroxide precursor.

[0092] In some embodiments, the molar ratio of the cathode material precursor to the lithium source in the mixture is 1:(1.01~1.08), for example, it can be 1:1.01, 1:1.02, 1:1.03, 1:1.04, 1:1.05, 1:1.06, 1:1.07 or 1:1.08, but is not limited to the listed values, other unlisted values ​​within this range are also applicable.

[0093] In some embodiments, the sintering process further includes a heating process at a heating rate of 1 to 10 °C / min. The heating rate may be, for example, 1 °C / min, 2 °C / min, 3 °C / min, 4 °C / min, 5 °C / min, 6 °C / min, 7 °C / min, 8 °C / min, 9 °C / min or 10 °C / min, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0094] In some embodiments, the sintering temperature is 690~850℃ and the time is 8~20h.

[0095] In this invention, the sintering temperature is 690~850℃, for example, it can be 690℃, 700℃, 725℃, 750℃, 775℃, 800℃, 825℃ or 850℃, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0096] In this invention, the sintering time is 8 to 20 hours, for example, it can be 8 hours, 9 hours, 10 hours, 10.5 hours, 11 hours, 11.5 hours, 12 hours, 12.5 hours, 13 hours, 13.5 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours or 20 hours, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0097] In some embodiments, the cathode material in step (1) is a polycrystalline material, including nickel-cobalt-manganese ternary cathode material, wherein the D50 particle size of the polycrystalline material is 2μm~15μm; the average particle size of the primary particles of the polycrystalline material is 300nm~1.1μm; and in step (1), the D50 particle size of the first coated raw material is smaller than the average particle size of the primary particles of the polycrystalline material. Alternatively, the cathode material in step (1) is a single crystal material, including nickel-cobalt-manganese ternary cathode material, and the D50 particle size of the single crystal material is 1.1μm~6μm; the D50 particle size of the first coated raw material in step (1) is smaller than the D50 particle size of the single crystal material. Alternatively, the cathode material in step (1) is a quasi-single crystal material, including nickel-cobalt-manganese ternary cathode material, and the D50 particle size of the quasi-single crystal material is 2μm~15μm; the D50 particle size of the first coated raw material in step (1) is smaller than the average particle size of the primary particles of the quasi-single crystal material. In some embodiments, in step (1), the D50 particle size of the first coated material is 30 nm to 1 μm; In some embodiments, the D50 particle size of the second coated material in step (2) is ≤15μm.

[0098] In this invention, when the cathode material in step (1) is a polycrystalline material, the D50 particle size of the polycrystalline material is 2μm~15μm, for example, it can be 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 12μm or 15μm, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0099] In this invention, when the cathode material in step (1) is a single crystal material, the D50 particle size of the single crystal material is independently 1.1μm to 6μm, for example, it can be 1.1μm, 1.5μm, 2.0μm, 2.5μm, 3.0μm, 3.5μm, 4.0μm, 4.5μm, 5.0μm, 5.5μm or 6.0μm, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0100] In this invention, when the cathode material in step (1) is a single-crystal-like material, the D50 particle size of the single-crystal-like material is 2μm~15μm, for example, it can be 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 12μm or 15μm, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0101] In this invention, by limiting the D50 particle size to 2μm~15μm when the cathode material is polycrystalline, 1.1μm~6μm when the cathode material is monocrystalline, and 2μm~15μm when the cathode material is quasi-monocrystalline, the D50 particle size can be precisely adapted to the intrinsic structural characteristics of polycrystalline, monocrystalline, and quasi-monocrystalline cathode materials. This provides a suitable particle morphology and specific surface area substrate for two-step coating modification, ensuring that the first coating layer is uniformly anchored on the particle surface to form an island-like distribution, while improving the coverage of the second coating layer and enhancing the coating uniformity. It can also shorten the lithium-ion diffusion path, suppress the initiation of intergranular cracks and coating layer detachment during cycling, and reduce electrolyte side reactions.

[0102] In this invention, the polycrystalline material refers to secondary particles formed by the agglomeration of a large number of primary particles, with each secondary particle containing no less than 50 primary particles; the quasi-single-crystal material refers to secondary particles formed by the agglomeration of a small number of large-sized primary particles, with each secondary particle containing 2-40 primary particles; and the single-crystal material refers to independently existing primary particles.

[0103] In this invention, the D50 particle size of the first coated material in step (1) is 30nm~1μm, for example, it can be 30nm, 50nm, 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm or 1μm, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0104] In this invention, the D50 particle size of the second coated material in step (2) is ≤15μm, for example, it can be 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm or 15μm, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0105] In this invention, in step (1), the D50 particle size of the first coating material is smaller than the average particle size of the primary particles of the polycrystalline material or the single-crystal-like material, or smaller than the D50 particle size of the single-crystal material. Combined with the temperature of the first heat treatment being less than the melting point of the first coating material, this ensures that the first coating material does not melt during the first heat treatment. It is distributed in an island-like pattern on the surface of the cathode material, which increases the surface roughness of the cathode material. This is beneficial for the coating of the first coating material after melting, and improves the coating rate of the composite cathode material coating layer.

[0106] In this invention, the D50 particle size of the cathode material affects the performance of the composite cathode material and the battery. When the cathode material is a single crystal material, and the D50 particle size of the single crystal material is 1.1 μm to 6 μm, the composite cathode material and the battery exhibit better performance. This is because when the D50 particle size of the single crystal material is within this range, it can ensure that the composite cathode material has a shorter ion transport particle size, thereby enabling the battery to achieve a higher capacity. At the same time, it can also facilitate the coating of the cathode material by the coating material, thereby effectively suppressing the side reactions between the composite cathode material and the solid electrolyte.

[0107] In this invention, when the D50 particle size of the first coating material is 30nm~1μm, the composite cathode material and battery exhibit better performance. This is because when the D50 particle size of the first coating material is within this range, the size of the first coating material is smaller than the average particle size of the primary particles of the cathode material. The first coating material, which does not melt during the first heat treatment, forms a protrusion composed of a third coating material on the surface of the cathode material, thereby helping to achieve the coating of the cathode material after the second coating material melts.

[0108] In this invention, when the D50 particle size of the second coating material is ≤15μm, the composite cathode material and the battery exhibit better performance. This is because when the D50 particle size of the first coating material is ≤15μm, the increased melting difficulty and reduced fluidity caused by the excessive size of the first coating material are avoided, which is not conducive to coating the cathode material.

[0109] In some implementations, in the mixing described in step (1), the mass ratio of the cathode material to the first coating material is 1:(0.005~0.05); And / or, in the mixing described in step (2), the mass ratio of the first material obtained in step (1) to the second coating material is 1:(0.0005~0.005); And / or, in step (1), the first coating material includes any one or a combination of at least two of cobalt oxide, cobalt arsenide, zirconate or silicate; And / or, in step (2), the second coating material includes boric acid and / or silicic acid.

[0110] In this invention, by limiting the mass ratio of the positive electrode material to the first coating material and the mass ratio of the first material to the second coating material, the composition of the first coating material and the second coating material is further limited. Furthermore, by further limiting the temperature and time of the first heat treatment and the second heat treatment, the following effects can be achieved: In the first heat treatment, part of the first coating material reacts to generate the third coating material, while part does not react, thereby forming a first coating layer containing the third coating material and the first coating material; at the same time, in the second heat treatment, part of the second coating material reacts to generate the fourth coating material, while part does not react, thereby forming a second coating layer containing the fourth coating material and the second coating material.

[0111] Furthermore, in this invention, by limiting the mass ratio of the positive electrode material to the first coating material in the mixture described in step (1), the beneficial effect is that while reducing surface residual alkali and enhancing the conductivity of electrons, the coating layer is avoided to prevent the impedance growth problem caused by the thickness.

[0112] Furthermore, in this invention, by limiting the mass ratio of the first material to the second coating material in the mixture described in step (2), the beneficial effect is that while enhancing the ion conduction capability, the coating layer is avoided to be too thick, so as to prevent the impedance growth problem caused by the thickness.

[0113] Furthermore, in this invention, the first coating material is defined as any one or a combination of at least two of cobalt oxide, cobalt arsenide, zirconate, or silicate. This is because cobalt oxide, cobalt arsenide, zirconate, or silicate have high melting points and can remain unmelted during the first heat treatment, thereby achieving an island-like distribution on the surface of the cathode material. In addition, cobalt oxide, cobalt arsenide, zirconate, or silicate themselves have high hardness. The presence of unreacted cobalt oxide, cobalt arsenide, zirconate, or silicate as the first coating material in the first coating layer can improve the internal strength of the composite cathode material.

[0114] Furthermore, in this invention, the second coating material is defined as boric acid and / or silica, because boric acid and / or silica have a low melting point and can melt during the second heat treatment, thereby achieving interlocking with the first coating layer and improving the coating effect of the second coating layer; in addition, boric acid and / or silica themselves have low hardness, and the unreacted boric acid and / or silica exist as the second coating material in the second coating layer, which can improve the flexibility of the second coating layer and achieve flexible contact between the composite cathode material and the solid electrolyte.

[0115] In this invention, in the mixing process described in step (1), the mass ratio of the positive electrode material to the first coating material is 1:(0.005~0.05), for example, it can be 1:0.005, 1:0.01, 1:0.015, 1:0.02, 1:0.025, 1:0.03, 1:0.035, 1:0.04, 1:0.045 or 1:0.05, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0116] In this invention, during the mixing process described in step (2), the mass ratio of the first material obtained in step (1) to the second coating material is 1:(0.0005~0.005), for example, it can be 1:0.0005, 1:0.001, 1:0.0015, 1:0.002, 1:0.0025, 1:0.003, 1:0.0035, 1:0.004, 1:0.0045 or 1:0.005, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0117] In this invention, the first coating material includes any one or a combination of at least two of cobalt oxide, cobalt arsenide, zirconate, or silicate. Typical but non-limiting combinations include a combination of cobalt oxide and cobalt arsenide, a combination of zirconate and silicate, a combination of cobalt arsenide and zirconate, or a combination of cobalt oxide, zirconate, and silicate.

[0118] In this invention, the cobalt oxide in the first coating material includes any one or a combination of at least two of cobalt trioxide, cobalt monoxide, or cobalt trioxide. Typical but non-limiting combinations include a combination of cobalt trioxide and cobalt monoxide, a combination of cobalt monoxide and cobalt trioxide, a combination of cobalt trioxide and cobalt trioxide, or a combination of cobalt trioxide, cobalt monoxide, and cobalt trioxide.

[0119] In this invention, the zirconate in the first coating material includes any one or a combination of at least two of calcium zirconate, strontium zirconate, barium zirconate, lanthanum zirconate, or yttrium zirconate. Typical but non-limiting combinations include combinations of calcium zirconate and strontium zirconate, combinations of strontium zirconate and barium zirconate, combinations of lanthanum zirconate and yttrium zirconate, or combinations of calcium zirconate, strontium zirconate, and barium zirconate.

[0120] In this invention, the silicate in the first coating material includes zirconium silicate and / or sodium silicate.

[0121] In another embodiment, the present invention provides a battery comprising the above-described composite positive electrode material, wherein the battery is an all-solid-state battery.

[0122] The numerical range described in this invention includes not only the point values ​​listed above, but also any point values ​​within the numerical ranges not listed above. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values ​​included in the range.

[0123] Example 1 This embodiment provides a composite cathode material, which includes a cathode material core, a first coating layer with island-like distribution on the surface of the cathode material core, and a second coating layer that at least partially covers the cathode material core and / or the first coating layer. The cathode material in the cathode material core is a single-crystal material with the chemical formula LiNi. 0.93 Co 0.06 Mn 0.01 O2; The first coating layer includes a first coating material (cobalt suboxide) with a Mohs hardness of 5.6 and a third coating material (lithium cobalt oxide, with an electrical conductivity of 10). -3 ~10 -1 S / cm); The second coating layer includes a second coating material (boric acid) with a Mohs hardness of 1.0 and a fourth coating material (lithium borate, with an electrical conductivity of 10). -6 S / cm); The first coating layer and the second coating layer cover 84% of the surface area of ​​the cathode material core; The preparation method of the composite cathode material includes: (1) A D50 hydroxide precursor with a particle size of 4 μm and a molar ratio of 1:1.04 (chemical formula Ni) was used. 0.93 Co 0.06 Mn 0.01 (OH)₂ was mixed with lithium hydroxide and sintered at 800°C for 12 hours in an oxygen-containing atmosphere with an oxygen volume fraction of 90%, with a heating rate of 5°C / min. The resulting cathode material (a single-crystal material with the chemical formula LiNi) was obtained. 0.93 Co 0.06 Mn 0.01 O2, the D50 particle size of the single crystal material is shown in Table 2); The obtained cathode material was tested using a scanning electron microscope, and the SEM image of the cathode material is shown below. Figure 1 As shown; by Figure 1 It can be seen that the cathode material is a single crystal; (2) After mixing the positive electrode material obtained in step (1) with D50 particle size of 500nm (melting point of 1935℃) in a mass ratio of 1:0.01, the material is heated to 700℃ at a heating rate of 5℃ / min in an oxygen-containing atmosphere with a volume fraction of 90% and then subjected to a first heat treatment for 12h. Then, the material is crushed and sieved in sequence to obtain the first material. In the first heat treatment, some of the cobalt oxide reacts to form lithium cobalt oxide, while some of the cobalt oxide does not react. (3) After mixing the first material obtained in step (2) with a mass ratio of 1:0.001 with boric acid (melting point of 170.9℃) with a D50 particle size of 10μm, the mixture is heated to 400℃ at a heating rate of 5℃ / min in an oxygen-containing atmosphere with a volume fraction of 90% and then subjected to a second heat treatment for 12h. The mixture is then crushed and sieved in sequence to obtain the composite cathode material. In the second heat treatment, some boric acid reacts to form lithium borate, while some boric acid does not react.

[0124] The obtained composite cathode material was tested using the BSE mode of a scanning electron microscope, and the SEM image of the composite cathode material is shown below. Figure 2 As shown; Figure 2 The black area in the middle is the second coating layer.

[0125] Example 2 This embodiment provides a composite cathode material, which includes a cathode material core, a first coating layer with island-like distribution on the surface of the cathode material core, and a second coating layer that at least partially covers the cathode material core and / or the first coating layer. The cathode material in the cathode material core includes a polycrystalline material with the chemical formula LiNi. 0.93 Co 0.06Mn 0.01 O2; The first coating layer includes a first coating material (calcium zirconate) with a Mohs hardness of 7.0 and a third coating material (lithium zirconate with an electrical conductivity of 10). -3 ~10 -6 S / cm); The second coating layer includes a second coating material (silicic acid) with a Mohs hardness of 1.0 and a fourth coating material (lithium silicate with a conductivity of 10). -6 ~10 -5 S / cm); The first coating layer and the second coating layer cover 84% of the surface area of ​​the cathode material core; The preparation method of the composite cathode material includes: (1) A hydroxide precursor with a D50 particle size of 4 μm (chemical formula Ni) with a molar ratio of 1:1.01 was used. 0.93 Co 0.06 Mn 0.01 (OH)₂ is mixed with lithium hydroxide and then sintered at 700°C for 14 hours in an oxygen-containing atmosphere with an oxygen volume fraction of 80% at a heating rate of 1°C / min to obtain a positive electrode material (the positive electrode material is a polycrystalline material with the chemical formula LiNi). 0.93 Co 0.06 Mn 0.01 O2, the average particle size of the primary particles and the D50 particle size of the secondary particles of the polycrystalline material are shown in Table 3). (2) After mixing the positive electrode material obtained in step (1) with a mass ratio of 1:0.05 and the first coating material (calcium zirconate with a D50 particle size of 30nm, melting point of 2200~2550℃), the material is heated to 650℃ at a heating rate of 1℃ / min in an oxygen-containing atmosphere with an oxygen volume fraction of 80% and then subjected to a first heat treatment for 14h. The material is then crushed and sieved in sequence to obtain the first material. In the first heat treatment, some calcium zirconate reacts to form lithium zirconate, while some calcium zirconate does not react; (3) After mixing the first material obtained in step (2) with a mass ratio of 1:0.005 with silica (melting point of 150℃) with a D50 particle size of 5μm, the material is heated to 400℃ at a heating rate of 1℃ / min in an oxygen-containing atmosphere with an oxygen volume fraction of 80% and then subjected to a second heat treatment for 14h. The material is then crushed and sieved in sequence to obtain the composite cathode material. In the second heat treatment, some of the silicic acid reacts to form lithium silicate, while some of the silicic acid does not react.

[0126] Example 3 This embodiment provides a composite cathode material, which includes a cathode material core, a first coating layer with island-like distribution on the surface of the cathode material core, and a second coating layer that at least partially covers the cathode material core and / or the first coating layer. The cathode material in the cathode material core includes a single-crystal material with the chemical formula LiNi. 0.93 Co 0.06 Mn 0.01 O2; The first coating layer includes a first coating material (sodium silicate) with a Mohs hardness of 5.5 and a third coating material (lithium silicate with an electrical conductivity of 10). -6 ~10 -5 S / cm); The second coating layer includes a second coating material (boric acid) with a Mohs hardness of 1 and a fourth coating material (lithium borate, with an electrical conductivity of 10). -6 S / cm); The first coating layer and the second coating layer cover more than 80% of the surface area of ​​the cathode material core; The preparation method of the composite cathode material includes: (1) A hydroxide precursor with a D50 particle size of 4 μm and a molar ratio of 1:1.08 (chemical formula Ni) was used. 0.93 Co 0.06 Mn 0.01 (OH)₂ is mixed with lithium hydroxide and then sintered at 850°C for 10 hours in an oxygen-containing atmosphere with an oxygen volume fraction of 90% at a heating rate of 10°C / min to obtain a cathode material (the cathode material is a single crystal material with the chemical formula LiNi). 0.93 Co 0.06 Mn 0.01 O2, the D50 particle size of the single crystal material is shown in Table 2); (2) After mixing the positive electrode material obtained in step (1) with a mass ratio of 1:0.005 and the first coating material (sodium silicate with a D50 particle size of 1μm, melting point of 1200℃~1410℃), the material is heated to 800℃ at a heating rate of 10℃ / min in an oxygen-containing atmosphere with an oxygen volume fraction of 90% and then subjected to a first heat treatment for 10h. The material is then crushed and sieved in sequence to obtain the first material. In the first heat treatment, some sodium silicate reacts to form lithium silicate, while some sodium silicate does not react. (3) After mixing the first material obtained in step (2) with a mass ratio of 1:0.005 and boric acid with a D50 particle size of 15μm (melting point of 170.9℃), the mixture is heated to 600℃ at a heating rate of 10℃ / min in an oxygen-containing atmosphere with an oxygen volume fraction of 90% and then subjected to a second heat treatment for 10h. The mixture is then crushed and sieved in sequence to obtain the composite cathode material. In the second heat treatment, some boric acid reacts to form lithium borate, while some boric acid does not react.

[0127] Example 4 This embodiment provides a composite cathode material, wherein the first coating layer includes a first coating material (strontium zirconate) with a Mohs hardness of 7.5 and a third coating material (lithium zirconate with a conductivity of 10). -3 ~10 -6 S / cm); The second coating layer includes a second coating material (silicic acid) with a Mohs hardness of 1.0 and a fourth coating material (lithium silicate with a conductivity of 10). -6 ~10 -5 S / cm); Except for replacing cobalt oxide (melting point 1935°C) with strontium zirconate (melting point 2600°C) in step (2) of the method for preparing the composite cathode material, and replacing boric acid (melting point 170.9°C) with silicic acid (melting point 150°C) in step (3), the rest are the same as in Example 1.

[0128] Example 5 This embodiment provides a composite cathode material, wherein the cathode material in the cathode material core is a near-single-crystal material with the chemical formula LiNi. 0.93 Co 0.06 Mn 0.01 O2, except for the D50 particle size of the single-crystal-like material shown in Table 3, is the same as in Example 1; The preparation method of the composite cathode material includes: (1) A hydroxide precursor with a D50 particle size of 4 μm and a molar ratio of 1:1.02 (chemical formula Ni) was used. 0.93 Co 0.06 Mn 0.01 (OH)₂ is mixed with a lithium source and then sintered at 750°C for 12 hours in an oxygen-containing atmosphere with an oxygen volume fraction of not less than 60%, with a heating rate of 5°C / min, to obtain a cathode material (the cathode material is a quasi-single crystal material with the chemical formula LiNi). 0.93 Co 0.06 Mn 0.01 O2, the D50 particle size of the quasi-single crystal material is shown in Table 2); (2) After mixing the positive electrode material obtained in step (1) with D50 particle size of 500nm (melting point of 1935℃) in a mass ratio of 1:0.01, the material is heated to 700℃ at a heating rate of 5℃ / min in an oxygen-containing atmosphere with a volume fraction of 90% and then subjected to a first heat treatment for 12h. Then, the material is crushed and sieved in sequence to obtain the first material. In the first heat treatment, some of the cobalt oxide reacts to form lithium cobalt oxide, while some of the cobalt oxide does not react. (3) After mixing the first material obtained in step (2) with a mass ratio of 1:0.001 with boric acid (melting point of 170.9℃) with a D50 particle size of 10μm, the mixture is heated to 400℃ at a heating rate of 5℃ / min in an oxygen-containing atmosphere with a volume fraction of 90% and then subjected to a second heat treatment for 12h. The mixture is then crushed and sieved in sequence to obtain the composite cathode material. In the second heat treatment, some boric acid reacts to form lithium borate, while some boric acid does not react.

[0129] Example 6 This embodiment provides a composite cathode material, wherein the cathode material in the cathode material core is a polycrystalline material with the chemical formula LiNi. 0.93 Co 0.06 Mn 0.01 O2, except that the average particle size of the primary particles and the D50 particle size of the secondary particles of the polycrystalline material are shown in Table 3, are the same as in Example 1. The preparation method of the composite cathode material includes: (1) A hydroxide precursor with a D50 particle size of 4 μm and a molar ratio of 1:1.04 (chemical formula Ni) was used. 0.93 Co 0.06 Mn 0.01 (OH)₂ is mixed with a lithium source and then sintered at 700°C for 12 hours in an oxygen-containing atmosphere with an oxygen volume fraction of not less than 60%, with a heating rate of 5°C / min, to obtain a positive electrode material (the positive electrode material is a polycrystalline material with the chemical formula LiNi). 0.93 Co 0.06 Mn 0.01 O2, the D50 particle size of the polycrystalline material is shown in Table 3); (2) After mixing the positive electrode material obtained in step (1) with D50 particle size of 500nm (melting point of 1935℃) in a mass ratio of 1:0.01, the material is heated to 700℃ at a heating rate of 5℃ / min in an oxygen-containing atmosphere with a volume fraction of 90% and then subjected to a first heat treatment for 12h. Then, the material is crushed and sieved in sequence to obtain the first material. In the first heat treatment, some of the cobalt oxide reacts to form lithium cobalt oxide, while some of the cobalt oxide does not react. (3) After mixing the first material obtained in step (2) with a mass ratio of 1:0.001 with boric acid (melting point of 170.9℃) with a D50 particle size of 10μm, the mixture is heated to 400℃ at a heating rate of 5℃ / min in an oxygen-containing atmosphere with a volume fraction of 90% and then subjected to a second heat treatment for 12h. The mixture is then crushed and sieved in sequence to obtain the composite cathode material. In the second heat treatment, some boric acid reacts to form lithium borate, while some boric acid does not react.

[0130] Example 7 This embodiment provides a composite cathode material. Except for step (1) of the preparation method of the composite cathode material, in which the D50 particle size of the hydroxide precursor is 4 μm and the sintering temperature is 780℃, and the D50 particle size of the single crystal material is shown in Table 2, all other aspects are the same as in Example 1.

[0131] Example 8 This embodiment provides a composite cathode material. Except for the cobalt suboxide with a D50 particle size of 30 nm used in step (2) of the preparation method of the composite cathode material, the rest is the same as in Example 1.

[0132] Example 9 This embodiment provides a composite cathode material. Except for the cobalt suboxide with a D50 particle size of 1 μm used in step (2) of the preparation method of the composite cathode material, the rest is the same as in Example 1.

[0133] Example 10 This embodiment provides a composite cathode material. Except for the boric acid with a D50 particle size of 5 μm used in step (3) of the preparation method of the composite cathode material, the rest is the same as in Example 1.

[0134] Example 11 This embodiment provides a composite cathode material. Except for the fact that the D50 particle size of the hydroxide precursor is 15 μm and the sintering temperature is 920 °C in step (1) of the preparation method of the composite cathode material, and the D50 particle size of the obtained single crystal material is shown in Table 2, the rest are the same as in Example 1.

[0135] The cathode material obtained in step (1) of the composite cathode material preparation method described in this embodiment was tested using a scanning electron microscope, and the SEM image of the cathode material is shown below. Figure 3 As shown; by Figure 3 It can be seen that the cathode material is a large single crystal.

[0136] Example 12 This embodiment provides a composite cathode material. Except for the fact that the D50 particle size of the hydroxide precursor is 15 μm and the sintering temperature is 1050℃ in step (1) of the preparation method of the composite cathode material, and the D50 particle size of the obtained single crystal material is shown in Table 2, the rest are the same as in Example 1.

[0137] Example 13 This embodiment provides a composite cathode material. Except for the cobalt suboxide with a D50 particle size of 20 nm used in step (2) of the preparation method of the composite cathode material, the rest is the same as in Example 1.

[0138] Example 14 This embodiment provides a composite cathode material. Except for the cobalt suboxide with a D50 particle size of 2 μm used in step (2) of the preparation method of the composite cathode material, the rest is the same as in Example 1.

[0139] Example 15 This embodiment provides a composite cathode material. Except for the cobalt suboxide with a D50 particle size of 3 μm used in step (2) of the preparation method of the composite cathode material, the rest is the same as in Example 1.

[0140] Example 16 This embodiment provides a composite cathode material. Except for the boric acid with a D50 particle size of 30 μm used in step (3) of the preparation method of the composite cathode material, the rest is the same as in Example 1.

[0141] Example 17 This embodiment provides a composite cathode material. Except for step (1) of the preparation method of the composite cathode material, the D50 particle size of the hydroxide precursor is 2 μm, and it is heated to 690℃ at a heating rate of 1℃ / min and then sintered for 10 h to obtain the cathode material (the cathode material is a polycrystalline material with the chemical formula LiNi). 0.93 Co 0.06 Mn 0.01 Except for O2 (the average particle size of the primary particles and the D50 particle size of the secondary particles of the polycrystalline material are shown in Table 3), everything else is the same as in Example 2.

[0142] Example 18 This embodiment provides a composite cathode material. Except for step (1) of the preparation method of the composite cathode material, the D50 particle size of the hydroxide precursor is 15 μm, and it is sintered for 20 h after being heated to 720℃ at a heating rate of 1℃ / min to obtain the cathode material (the cathode material is a polycrystalline material with the chemical formula LiNi). 0.93 Co 0.06 Mn 0.01Except for O2 (the average particle size of the primary particles and the D50 particle size of the secondary particles of the polycrystalline material are shown in Table 3), everything else is the same as in Example 2.

[0143] Example 19 This embodiment provides a composite cathode material. Except for step (1) of the preparation method of the composite cathode material, the D50 particle size of the hydroxide precursor is 4 μm. After heating to 800℃ at a heating rate of 5℃ / min, it is sintered for 8 hours to obtain the cathode material (the cathode material is a single crystal material with the chemical formula LiNi). 0.93 Co 0.06 Mn 0.01 Except for O2 (the D50 particle size of the single crystal material is shown in Table 2), everything else is the same as in Example 1.

[0144] Example 20 This embodiment provides a composite cathode material. Except for step (1) of the preparation method of the composite cathode material, the D50 particle size of the hydroxide precursor is 10 μm, and it is heated to 800℃ at a heating rate of 5℃ / min and then sintered for 20 h to obtain the cathode material (the cathode material is a single crystal material with the chemical formula LiNi). 0.93 Co 0.06 Mn 0.01 Except for O2 (the D50 particle size of the single crystal material is shown in Table 2), everything else is the same as in Example 1.

[0145] Example 21 This embodiment provides a composite cathode material. Except for step (1) of the preparation method of the composite cathode material, the D50 particle size of the hydroxide precursor is 2 μm, and it is heated to 740°C at a heating rate of 5°C / min and then sintered for 12 hours to obtain the cathode material (the cathode material is a quasi-single crystal material with the chemical formula LiNi). 0.93 Co 0.06 Mn 0.01 Except for O2 (the D50 particle size of the quasi-single crystal material is shown in Table 2), everything else is the same as in Example 1.

[0146] Example 22 This embodiment provides a composite cathode material. Except for step (1) of the preparation method of the composite cathode material, the D50 particle size of the hydroxide precursor is 15 μm, and it is heated to 780°C at a heating rate of 5°C / min and then sintered for 14 h to obtain the cathode material (the cathode material is a quasi-single crystal material with the chemical formula LiNi). 0.93 Co 0.06 Mn 0.01 Except for O2 (the D50 particle size of the quasi-single crystal material is shown in Table 2), everything else is the same as in Example 1.

[0147] Example 23 This embodiment provides a composite cathode material, wherein the cathode material core is a single-crystal material with the chemical formula LiNi. 0.6 Co 0.2 Mn 0.2 O2; The hydroxide precursor (chemical formula Ni) in step (1) of the method for preparing the composite cathode material is... 0.93 Co 0.06 Mn 0.01 (OH)2) is replaced with a hydroxide precursor (chemical formula Ni) of the same D50 particle size. 0.6 Co 0.2 Mn 0.2 (OH)2), heated to 920℃ at a heating rate of 5℃ / min and then sintered for 12h.

[0148] Comparative Example 1 This comparative example provides a composite cathode material, which includes a cathode material core, a first coating layer on the surface of the cathode material core, and a second coating layer covering the cathode material core and the first coating layer. The cathode material in the cathode material core is a single-crystal material with the chemical formula LiNi. 0.93 Co 0.06 Mn 0.01 O2; The first coating layer consists only of lithium borate and boric acid; The second coating layer includes lithium cobalt oxide and cobalt oxide; Except for replacing the first coating material in step (2) of the method for preparing the composite cathode material with boric acid (melting point 170.9℃) and the temperature of the first heat treatment with 400℃; and replacing the second coating material in step (3) with cobalt oxide (melting point 1935℃) and the temperature of the second heat treatment in step (3) with 700℃, the rest are the same as in Example 1.

[0149] Comparative Example 2 This comparative example provides a composite cathode material, except that the first coating layer in the composite cathode material is omitted; Except for step (2) of the preparation method of the composite cathode material, the rest is the same as in Example 1.

[0150] Comparative Example 3 This comparative example provides a composite cathode material, except that the first coating layer and the second coating layer in the composite cathode material are omitted. Except for steps (2) and (3) of the preparation method of the composite cathode material, the rest are the same as in Example 1.

[0151] Comparative Example 4 This comparative example provides a composite cathode material, except that the second coating layer in the composite cathode material is omitted; Except for step (3) of the preparation method of the composite cathode material, the rest is the same as in Example 1.

[0152] In the above embodiments 1 to 6, during the first heat treatment, part of the first coating material reacts to generate the third coating material, while part does not react, thereby forming a first coating layer containing the third coating material and the first coating material; therefore, by testing the Mohs hardness of the first coating material, the Mohs hardness of the first coating material can be obtained. In the above embodiments 1 to 6, during the second heat treatment, some of the second coating material reacts to generate the fourth coating material, while some does not react, thereby forming a second coating layer containing the fourth coating material and the second coating material; therefore, by testing the Mohs hardness of the second coating material, the Mohs hardness of the second coating material can be obtained.

[0153] The Mohs hardness test method is as follows: The indentation method is used. A hardness tester is employed, and a pyramidal diamond indenter is vertically pressed into the sample surface under a preset load (200 gf) and held for 12 seconds. After unloading, the diagonal length of the indentation is measured using a microscope. The result is calculated using the formula HK = 14.229 × P / d. 2 The Mohs hardness values ​​were calculated (P is the load, d is the diagonal length), and the calculated Mohs hardness values ​​are shown in Table 1.

[0154] Table 1 In step (1) of the preparation method of the composite cathode material provided in the above embodiments and comparative examples, the average particle size of the primary particles of the polycrystalline cathode material or quasi-single crystal, the D50 particle size of the agglomerated secondary particles, and the D50 particle size of the single crystal cathode material are tested. The test method for the D50 particle size of the cathode material is as follows: by using a Malvern laser particle size analyzer, the intensity of scattered light at different angles is measured, and by substituting into a suitable scattering theory, the D50 particle sizes of the single crystal material, quasi-single crystal material, and polycrystalline material in the cathode material are obtained as shown in Tables 2 and 3. The average particle size of the primary particles in polycrystalline cathode materials is determined by measuring the particle size of 200 primary particles within a SEM image and calculating the average value. The average particle size of the primary particles in quasi-monocrystalline cathode materials is determined by measuring the particle size of 50 primary particles within a SEM image and calculating the average value. The average particle sizes of the primary particles in the quasi-monocrystalline cathode materials and polycrystalline cathode materials are shown in Table 3. Furthermore, in step (1) of the composite cathode material preparation method, the D50 particle size of the obtained cathode material is basically fixed and remains largely unchanged in subsequent steps. Therefore, in the final composite cathode material, the D50 particle sizes of the monocrystalline, polycrystalline, and quasi-monocrystalline materials in the cathode material core are basically the same as the D50 particle sizes of the cathode materials obtained in the corresponding preparation methods.

[0155] Table 2 Table 3 The compressive strength of the composite cathode materials provided in the above embodiments and comparative examples was tested. The test method was as follows: a micron-level indenter was used to apply uniform pressure to a single cathode particle, and the force-displacement curve was recorded. The particle crushing was determined by the abrupt change point of the curve, and the compressive strength was calculated as shown in Tables 4 to 7. Among them, the compressive strength of the composite cathode material in which the cathode material in the cathode material core is a single crystal material is shown in Table 4; the compressive strength of the composite cathode material in which the cathode material in the cathode material core is a polycrystalline material is shown in Table 5; the compressive strength of the composite cathode material in which the cathode material in the cathode material core is a near-single crystal material is shown in Table 6; and the compressive strength of the cathode material in which the cathode material core is a medium-nickel single crystal material is shown in Table 7.

[0156] Table 4 Table 5 Table 6 Table 7 The coating ratio is calculated as follows: the ratio of the total molar amount of coated elements in the first and second coating layers to the total molar amount of all elements except lithium and oxygen in the first and second coating layers, i.e.: Coverage = n 包覆元素 / n 非Li和O ; Where, n 包覆元素 This represents the sum of the molar amounts of the coating elements contained in the first and second coating layers. Coating elements refer to the sum of the molar amounts of all elements (e.g., cobalt, zirconium, boron, silicon, etc.) except for lithium, oxygen, nickel, manganese, and cathode material doping elements (e.g., magnesium, titanium, calcium, strontium, etc.); n 非Li和O It represents the sum of the molar amounts of all elements except lithium and oxygen contained in the first and second coating layers.

[0157] It should be noted that the cathode material core does not necessarily contain doped elements. Whether the cathode material core contains doped elements can be determined by ICP combined with EDS testing. Both the cathode material core and the coating layer contain cobalt; here, cobalt is included in the coating layer elements for calculation.

[0158] The specific testing steps are as follows: (1) Determination of the total molar amount of coating elements: Take a composite cathode material sample and use X-ray photoelectron spectroscopy (XPS) combined with Ar + Ion etching was used for depth profiling, with the etching depth set at 100 nm (resulting in XPS images of the composite cathode materials provided in Example 1 and Comparative Example 1, as shown below). Figure 4 As shown, the XPS image of the first coating layer in the composite cathode material provided in Example 8 is as follows. Figure 5 As shown, the XPS image of the second coating layer in the composite cathode material provided in Example 8 is as follows. Figure 6 (As shown). Through XPS full-spectrum scanning and high-resolution narrow-spectrum quantitative analysis, the atomic percentage concentrations of all elements except lithium and oxygen in the first and second coating layers were obtained. Combined with parameters such as the etched area and material density, and excluding carbon as an interfering impurity, the molar amounts of each element were calculated. The molar amounts of all elements in all coating layers except lithium, oxygen, nickel, manganese, and dopants were summed to obtain n. 包覆元素 .

[0159] (2) Determination of the total molar amount of all elements in the coating layer except lithium and oxygen: Take a positive electrode material sample and use X-ray photoelectron spectroscopy (XPS) combined with Ar +Ion etching was used for depth profiling, with an etching depth set at 100 nm. Using XPS full-spectrum scanning and high-resolution narrow-spectrum quantitative analysis, the atomic percentage concentrations of all elements except lithium and oxygen in the first and second coating layers were obtained. Combined with parameters such as the etched area and material density, and excluding carbon as an interfering impurity, the molar amounts of each element were calculated. The molar amounts of all elements except lithium and oxygen in all coating layers were then summed to obtain n. 非Li和O .

[0160] (3) Substitute the values ​​obtained in steps (1) and (2) into the above formula to calculate the coverage rate. The coverage rates of each embodiment and comparative example are shown in Table 8.

[0161] Table 8 The composite cathode materials provided in the above embodiments and comparative examples were tested using X-ray photoelectron spectroscopy to obtain the elemental composition and molar ratio of each coating layer. The test results are shown in Table 9. The specific test methods are as follows: In XPS testing, using Ar + The ion gun performs in-situ etching on the sample surface at an etching rate calibrated to 2 nm / min using a standard sample. The etching depth is controlled by adjusting the total sputtering time, thereby reaching the depths of the first and second coating layers, respectively. (1) Testing of the first coating layer: The total sputtering time was set to 10 min, and the corresponding etching depth was 20 nm (10 min × 2 nm / min). XPS spectra were collected at this depth to characterize the element types and molar amounts of the first coating layer, and the molar ratio of the first coating material to the third coating material in the first coating layer was calculated. (2) Testing of the second coating layer: The total sputtering time was set to 50 min, and the corresponding etching depth was 100 nm (50 min × 2 nm / min). XPS spectra were collected at this depth to characterize the element types and molar amounts of the second coating layer, and the molar ratio of the second coating material to the fourth coating material in the second coating layer was calculated.

[0162] Table 9 The positive electrode sheet was prepared using the composite positive electrode material provided in the above embodiments and comparative examples. The method for preparing the positive electrode sheet is as follows: the composite positive electrode material, sulfide solid electrolyte, conductive carbon black, binder and water solvent provided in the above embodiments and comparative examples are mixed and the mass ratio of composite positive electrode material, sulfide solid electrolyte, conductive carbon black and binder is controlled to be 85:13:1:1 to obtain a positive electrode slurry. The obtained positive electrode slurry is coated on the surface of aluminum foil and then dried to obtain a positive electrode sheet.

[0163] The obtained positive electrode sheet is then used to prepare a mold battery. The method for preparing the mold battery is as follows: the obtained positive electrode sheet is used as the positive electrode, then graphite is used as the negative electrode, and sulfide solid electrolyte is used as the intermediate layer. After assembly, an all-solid-state mold battery is obtained.

[0164] Electrochemical performance tests were performed on the obtained mold batteries. The test voltage range was 2.5-4.25V, the current density was 1C, and the number of cycles was 500. The specific capacity of the coin cells at 1C initial discharge and the capacity retention rate after 500 cycles at 1C are shown in Tables 10-13. Among them, the specific capacity curves of the mold batteries prepared with the composite cathode materials provided in Examples 1, 3, 7, 9 and Comparative Example 3 are shown in Table 10-13. Figure 7 As shown.

[0165] The first material obtained in step (2) of the preparation method of the composite cathode material provided in Example 1 was tested using a scanning electron microscope. The SEM image obtained is shown below. Figure 8 As shown; by Figure 8 It can be seen that the first coating layer is distributed in an island-like pattern on the surface of the cathode material core, which increases the surface roughness of the cathode material core and is beneficial to the interlocking contact between the second coating layer and the first coating layer.

[0166] Table 10 Table 11 Table 12 Table 13 From Tables 1 to 13 and Figures 1-8 We can obtain: (1) In the composite cathode materials provided in Examples 1-10 and Examples 17-22, the first coating layer and the second coating layer have a high total coating rate on the cathode material core, and the battery prepared with the composite cathode material exhibits a high discharge specific capacity and excellent cycle stability. (2) By comparing Examples 1, 19, and 20 with Examples 11-12, it can be seen that in the preparation method of the composite cathode material in this invention, when the cathode material in step (1) is a single crystal material, the D50 particle size of the single crystal material will affect the performance of the composite cathode material and the battery. When the cathode material is a single crystal material, when the D50 particle size of the single crystal material is 1.1μm to 6μm, the composite cathode material and the battery exhibit better performance. This is because when the D50 particle size of the single crystal material is within this range, it can ensure that the composite cathode material has a shorter ion transport particle size, so that the battery can exert a higher capacity. At the same time, it can also help the coating material to coat the cathode material, thereby fully suppressing the side reaction between the composite cathode material and the solid electrolyte. When the D50 particle size of the single crystal material is too large, it will lead to an excessively high sintering temperature, resulting in high energy consumption of the preparation method and a low discharge specific capacity of the obtained cathode material and the battery containing the cathode material. (3) By comparing Examples 1, 8-9 with Examples 13-15, it can be seen that the D50 particle size of the first coating material used in the preparation method of the composite cathode material in this invention will affect the performance of the composite cathode material and the battery. When the D50 particle size of the first coating material is 30nm~1μm, the composite cathode material and the battery exhibit better performance. This is because when the D50 particle size of the first coating material is within this range, it can ensure that the second coating material has good fluidity after melting and has a large contact area with the primary particles of the cathode material, thereby improving the coating rate of the composite cathode material and fully suppressing the side reactions between the composite cathode material and the solid electrolyte. (4) By comparing Examples 1, 10 and Example 16, it can be seen that the D50 particle size of the second coating material used in the preparation method of the composite cathode material in this invention will affect the performance of the composite cathode material and the battery. When the D50 particle size of the second coating material is ≤15μm, the composite cathode material and the battery exhibit better performance. This is because the smaller particle size of the second coating material has better fluidity after being melted by heat treatment, which is conducive to improving the coating effect, making the coating of the second coating material more uniform and improving the coating rate, thereby reducing the side reaction between the composite cathode material and the solid electrolyte and improving the cycle stability of the battery. (5) As can be seen from the comparison between Example 1 and Comparative Examples 1 to 4, in the composite cathode material provided by the present invention, the first coating layer is distributed in an island-like manner on the surface of the cathode material core, which increases the surface roughness of the cathode material core and is conducive to the interlocking contact between the second coating layer and the first coating layer, thereby improving the coating effect of the second coating layer on the cathode material core and / or the outside of the first coating layer; therefore, in the composite cathode material, the coating of the cathode material by the first coating layer and the second coating layer is relatively uniform and has a high coating rate; therefore, when the battery containing the composite cathode material is used, the reaction intensity difference in different areas of the cathode material surface is small, and the side reactions between the composite cathode material and the solid electrolyte are sufficiently suppressed; therefore, the battery containing the composite cathode material exhibits high capacity and excellent cycle stability.

[0167] In the composite cathode material provided by the present invention, the first coating material in the first coating layer includes any one or a combination of at least two of cobalt oxide, cobalt arsenide, zirconate or silicate. These materials have a Mohs hardness of 3.0 to 9.0. Therefore, the first coating material with higher hardness has rigidity, which improves the internal strength of the composite cathode material, thereby improving the compressive strength of the composite cathode material and the cycle stability of the composite cathode material.

[0168] In the composite cathode material provided by the present invention, the second coating layer includes boric acid and / or silicic acid. These materials have a Mohs hardness of 1.0 to 3.0. Therefore, the second coating material with lower hardness is flexible, which improves the flexibility of the second coating layer and realizes flexible contact between the composite cathode material and the solid electrolyte, thereby enhancing the cycle stability of the composite cathode material.

[0169] In summary, the composite cathode material provided by this invention optimizes the bonding with the second coating layer through the island-like distribution of the first coating layer, achieving uniform and efficient coating. Furthermore, the first coating layer contains a high-hardness first coating material, enhancing internal strength and compressive strength, while the second coating layer contains a low-hardness, flexible second coating material, enabling flexible contact with the solid electrolyte. The synergistic effect of these two materials enhances cycle stability while ensuring the electrochemical activity of the composite cathode material. Therefore, batteries containing this composite cathode material exhibit high capacity and excellent cycle stability.

[0170] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A composite cathode material, characterized in that, The composite cathode material includes a cathode material core, a first coating layer with island-like distribution on the surface of the cathode material core, and a second coating layer that at least partially covers the cathode material core and / or the first coating layer. The core of the cathode material is composed of lithium transition metal oxide; The first coating layer includes a first coating material, which includes any one or a combination of at least two of cobalt oxide, cobalt arsenide, zirconate, or silicate. The second coating layer includes a second coating material, which includes boric acid and / or silica.

2. The composite cathode material according to claim 1, characterized in that, The first coating layer further includes a third coating material, which includes any one or a combination of at least two of lithium cobalt oxide, lithium zirconate, or lithium silicate; the first coating material and the third coating material do not contain the same material; And / or, the second coating layer further includes a fourth coating material, the fourth coating material including lithium borate and / or lithium silicate.

3. The composite cathode material according to claim 2, characterized in that, The molar ratio of the first coating material to the third coating material in the first coating layer is x:(10-x), and x is 0.1~4.

4. The composite cathode material according to claim 2, characterized in that, In the second coating layer, the molar ratio of the second coating material to the fourth coating material is y:(10-y), and y is 0.1~4.

5. The composite cathode material according to any one of claims 1 to 4, characterized in that, The first coating layer and the second coating layer cover more than 80% of the surface area of ​​the cathode material core.

6. A method for preparing the composite cathode material according to any one of claims 1 to 5, characterized in that, The preparation method includes: (1) After mixing the positive electrode material and the first coating raw material, a first heat treatment is carried out in an oxygen-containing atmosphere to obtain the first material; (2) After mixing the first material obtained in step (1) with the second coating material, a second heat treatment is carried out in an oxygen-containing atmosphere to obtain a composite cathode material; The cathode material is a lithium transition metal oxide cathode material; The temperature of the first heat treatment is less than the melting point of the first coating material; The melting point of the second coating material is less than the temperature of the second heat treatment; The temperature of the first heat treatment is 600℃~900℃, and the time is 10h~14h; The second heat treatment is performed at a temperature of 300℃ to 600℃ for a time of 10h to 14h.

7. The preparation method according to claim 6, characterized in that, The melting point of the second coating material is less than the temperature of the second heat treatment, which is less than the temperature of the first heat treatment, which is less than the melting point of the first coating material. And / or, the method for preparing the cathode material includes: mixing the cathode material precursor with a lithium source and then sintering it to obtain the cathode material; The temperature of the first heat treatment is lower than the temperature of the sintering.

8. The preparation method according to claim 6, characterized in that, The cathode material in step (1) is a polycrystalline material, including nickel-cobalt-manganese ternary cathode material. The D50 particle size of the polycrystalline material is 2μm~15μm; the average particle size of the primary particles of the polycrystalline material is 300nm~1.1μm; the D50 particle size of the first coated raw material in step (1) is smaller than the average particle size of the primary particles of the polycrystalline material. Alternatively, the cathode material in step (1) is a single crystal material, including nickel-cobalt-manganese ternary cathode material, and the D50 particle size of the single crystal material is 1.1μm~6μm; the D50 particle size of the first coated raw material in step (1) is smaller than the D50 particle size of the single crystal material. Alternatively, the cathode material in step (1) is a quasi-single crystal material, including nickel-cobalt-manganese ternary cathode material, and the D50 particle size of the quasi-single crystal material is 2μm~15μm; the D50 particle size of the first coated raw material in step (1) is smaller than the average particle size of the primary particles of the quasi-single crystal material. And / or, in step (1), the D50 particle size of the first coated material is 30 nm to 1 μm; And / or, in step (2), the D50 particle size of the second coated material is ≤15μm.

9. The preparation method according to any one of claims 6 to 8, characterized in that, In the mixing process described in step (1), the mass ratio of the cathode material to the first coating material is 1:(0.005~0.05); And / or, in the mixing described in step (2), the mass ratio of the first material obtained in step (1) to the second coating material is 1:(0.0005~0.005); And / or, in step (1), the first coating material includes any one or a combination of at least two of cobalt oxide, cobalt arsenide, zirconate or silicate; And / or, in step (2), the second coating material includes boric acid and / or silicic acid.

10. A battery, characterized in that, The battery includes the composite cathode material according to any one of claims 1 to 5, and the battery is an all-solid-state battery.